Traditional Fishing Rights for Bendega (Balinese Traditional Fisherman) - Ni Putu Suci Meinarni; Komang Redy Winatha; I Putu Hendika Permana (Jurnal Hukum Prasada, 2021)
Bendega is one of the cultural heritage of Balinese ancestors is a social organization whose existence has begun to decrease. This existence is closely related to their rights and obligations as part of the main community members in the coastal areas of Bali. This study aims to determine the rights and obligations of fishermen based on applicable regulations and to find out whether these rights and obligations have gone in harmony. This study used the normative-empirical legal research method. Normatively, this study is done through literature studies and empirically conducted by distributing random questionnaires to several fishermen in Bali. Based on the analysis, the results of this study showed that some fishermen have never read Local Government Regulations of Bali Number 11 year 2017 about Bendega. Some of them feel the right to catch fish is a result of business activities in other sectors. The effectiveness of legislation has not been running optimally. The community, especially the fishermen, need re-socialization related to their knowledge of Local Government Regulations of Bali Number 11 year 2017 about Bendega, so that they can find out more about their rights and obligations as Bendega.